Can rural climate services meet context-specific needs, and still be scalable? Experience from Rwanda - Hansen, James; Kagabo, Desire M.; Nsengiyumva, Gloriose (University of Cape Town, 2019)
Investment in national climate services must address trade-offs between meeting context-specific farmer needs and providing cost-effective services at scale. In the context of an ongoing national-scale agricultural climate service initiative in Rwanda, we discuss approaches used to address five scaling challenges (capacity constraints of farmers, communication intermediaries, climate information providers, data gaps, and co-production with farmers) and the resulting lessons.